Espécies de Meloidogyne Goeldi em cafeeiro no município de Araguari-MG - Carneiro, Franciele Alves [UNESP] (2014)
Araguari County represents one of the main national coffee production in Brazil. However, productivity is significantly affected by the parasitic root-knot nematodes which are cited as major pests for coffee plants. Therefore, this study was conducted in coffee plantations properties infested by nematodes in Araguari county, aiming to identify the present species. Soil and root samples from 18 coffee areas which presented depletion symptoms were collected and transported to the Laboratory of Nematologya, Departament of Plant Protection, UNESP/FCAV, Jaboticabal, SP for the study. The species were identified based on the morphology of the perineal pattern, morphology and morphometric of the lip males region, and also confirmed by esterase enzyme phenotype. In the studied populations, the identified species were: M. incognita which predominated in the plantations examined, followed by M. exigua, which was found in 5 properties sampled and M. paranaensis, found in only 3 samples. Also, in intermediate plants used as supplementary income like pumpkin (Cucurbita pepo L.), was found M. paranaensis and M. incognita. Moreover, a weed plant known as Momordica charantia L. was infected by a non-identified Meloidogyne specie. The information obtained in this study will be useful for developing these pest management programs